The Influence of Brand Image and Advertising Claims on Purchase Decision - Soedargo, Bayu; Mulya, Siti (Jurnal Ilmiah Manajemen Kesatuan, 2023)
The buying decision-making process will be influenced by brands and advertising. The term “brand image” relates to how people view a specific brand, whereas “advertising factors” refers to marketing methods used to sell items. The goal of this study is to determine whether Marina Hand and Body Lotion purchase decisions are influenced by brand perception, whether those decisions are also influenced by advertising claims, and whether those decisions are influenced by both brand perception and advertising jointly, particularly for Gen Z consumers who live in the city of Bogor. 130 respondents were chosen using a purposive selection technique, and the Hair et al. formula was applied. Respondents’ responses provided the information needed. The Statistical Package for the Social Sciences (SPSS), which employs the Multiple Linear Regression Analysis approach, was used to process the 130 respondents’ survey responses. The study discovered that: (1) Brand image significantly and favorably influenced customers’ decisions to buy Marina hand and body lotion; (2) Advertising claims significantly and favorably influenced customers’ decisions to buy Marina hand and body lotion; and (3) Overall, Marina’s brand image and advertising claims significantly and favorably influenced customers’ decisions to buy Marina hand and body lotion. ABSTRAK Merek dan iklan akan mempengaruhi proses keputusan pembelian. Faktor iklan adalah alat pemasaran untuk mempromosikan produk, sedangkan citra merek merujuk pada bagaimana konsumen melihat merek tertentu. Tujuan dari penelitian ini adalah untuk mengetahui apakah keputusan untuk membeli Hand and Body Lotion Marina dipengaruhi oleh citra merek, apakah keputusan tersebut juga dipengaruhi oleh iklan dan apakah keputusan tersebut dipengaruhi oleh citra merek dan iklan secara bersama, khususnya untuk pelanggan Gen Z yang tinggal di Kota Bogor. Metode pengambilan sampel purposive digunakan untuk memilih 130 responden, dan rumus Hair et al. digunakan. Data yang digunakan berasal dari jawaban responden. Jumlah data yang dikumpulkan dari kuesioner berjumlah 130 orang dan diproses menggunakan Statistical Package for the Social Sciences (SPSS), yang menggunakan metode Analisis Regresi Linier Berganda. Studi menemukan bahwa: (1) Keputusan pelanggan untuk membeli hand and body lotion Marina dipengaruhi secara signifikan dan positif oleh citra merek.; (2) Keputusan pelanggan untuk membeli hand and body lotion Marina dipengaruhi secara positif dan signifikan oleh iklan.; dan (3) Secara keseluruhan, citra merek dan iklan Marina berdampak positif dan signifikan pada keputusan pelanggan untuk membeli hand and body lotion Marina. Kata kunci: Citra Merek, Iklan, Keputusan Pembelian, Perilaku Konsumen, e-Commerce